2016
DOI: 10.1038/srep18642
|View full text |Cite
|
Sign up to set email alerts
|

Galangin sensitizes TRAIL-induced apoptosis through down-regulation of anti-apoptotic proteins in renal carcinoma Caki cells

Abstract: Galangin, bioflavonoids, has been shown anti-cancer properties in various cancer cells. In this study, we investigated whether galangin could enhance TRAIL-mediated apoptosis in TRAIL resistant renal carcinoma Caki cells. Galangin alone and TRAIL alone had no effect on apoptosis, while combined treatment with galangin and TRAIL significantly induced apoptosis in renal carcinoma (Caki, ACHN and A498) but not normal cells (normal mouse kidney cells and human normal mesangial cells). Galangin induced down-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Galangin, a flavonoid extracted from the root of Alpinia officinarum was reported to possess antiproliferative action and to inhibit renal cell carcinoma (786-0 and Caki-1) invasion by suppressing EMT, inducing apoptosis and producing ROS in renal carcinoma cells (Cao et al, 2016 ). Han et al ( 2016 ) observed that the combination of galangin and TRAIL significantly induced apoptosis in renal carcinoma (Caki, ACHN, and A498) but not in normal mouse kidney cells or human normal mesangial cells, suggesting the potential utilization of galangin as a sensitizer of TRAIL-resistant cancer cell therapy. Meng et al ( 2015 ) combined quercetin with anti-sense oligo gene therapy (Snail gene inhibition) and found that each suppressed the proliferation and migration of Caki-2 cells, inducing cell cycle arrest and apoptosis, with a strong suppression of renal carcinoma cells being achieved by their combination.…”
Section: Renal Carcinomamentioning
confidence: 99%
“…Galangin, a flavonoid extracted from the root of Alpinia officinarum was reported to possess antiproliferative action and to inhibit renal cell carcinoma (786-0 and Caki-1) invasion by suppressing EMT, inducing apoptosis and producing ROS in renal carcinoma cells (Cao et al, 2016 ). Han et al ( 2016 ) observed that the combination of galangin and TRAIL significantly induced apoptosis in renal carcinoma (Caki, ACHN, and A498) but not in normal mouse kidney cells or human normal mesangial cells, suggesting the potential utilization of galangin as a sensitizer of TRAIL-resistant cancer cell therapy. Meng et al ( 2015 ) combined quercetin with anti-sense oligo gene therapy (Snail gene inhibition) and found that each suppressed the proliferation and migration of Caki-2 cells, inducing cell cycle arrest and apoptosis, with a strong suppression of renal carcinoma cells being achieved by their combination.…”
Section: Renal Carcinomamentioning
confidence: 99%
“…On the contrary, human renal carcinoma (Caki) cells displayed a different kind of result when incubated with angelicin. Caki cells have always been known to be one of those cancer cell lines that are resistant to tumor necrosis factor (TNF) apoptosis inducing ligand (TRAIL) (Han et al, 2016). When the compound was tested alone, angelicin was not able to induce apoptosis, yet when incubated together with 50 ng/ml of TRAIL the combined treatment was able to promote cell death (Min et al, 2018).…”
Section: North America and Chinamentioning
confidence: 99%
“…However, a lot of cancer cells reveal resistance to TRAIL through multiple mechanisms, including down-regulation of death receptor (DR)4/5, and up-regulation of decoy death receptors and anti-apoptotic proteins [ 12 , 13 , 14 ]. New approaches to overcome TRAIL resistance that combined treatment with pharmacological agents that modify the function of tumor-dysregulated apoptotic genes have been investigated [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%